Feasibility of a quantitative literacy-based student worksheet for endocrine system practical lessons - Nambisas Arum Kusuma Ayu; Kurnia Ningsih; Anisyah Yuniarti; Mai Haruno (University of Muhammadiyah Malang, 2026)
Background: This research was prompted by the low level of quantitative literacy and science process skills (SPSs) among students, as well as the lack of teaching materials that support contextual endocrine system practical lessons. Objectives: This research aims to develop a student worksheet on the endocrine system based on quantitative literacy to train SPSs through data-based practical lessons. Methods: This research employed a Research & Development method, utilizing the Define, Design, Develop, and Disseminate (4D) development model, which is limited to the third stage. The instruments used in this research were an interview guide sheet, an instrument content validation sheet, and a student worksheet content validation sheet. Content validity analysis utilized Aiken’s validity index, while interrater reliability analysis employed the Intraclass Correlation Coefficient (ICC). Results: The content validity results showed an average Aiken’s validity index value of 0.98, indicating validity. Interrater reliability analysis using ICC yielded a value of 0.880 (good category). Conclusion: These findings indicate that the student worksheet is feasible and ready for use in the practical lessons on the endocrine system. It is recommended to conduct classroom trials to evaluate the effectiveness of the student worksheet in improving quantitative literacy, SPSs, and understanding of the endocrine system.